Assessing the Global Cultivation Practices of Kappaphycus alvarezii: A Comprehensive Review of Growth Dynamics, Nutrient Management, and Biochemical Composition - Sri Mulyani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Kappaphycus alvarezii is a crucial species for carrageenan production, widely used in various industries. This review aims to synthesize global research on the cultivation of K. alvarezii, focusing on growth dynamics, nutrient management, and biochemical composition. Studies show that growth rates are significantly influenced by cultivation methods, such as longline, raft farming, and Integrated Multi-Trophic Aquaculture (IMTA), each offering distinct advantages in terms of yield and ecological sustainability. Nutrient management, particularly nitrogen and phosphorus level, plays a critical role in optimizing both biomass and carrageenan quality. The use of biostimulants and fertilizers has been found to enhance growth and biochemical properties, yet careful nutrient control is essential to prevent negative environmental impacts such as eutrophication. Genetic diversity, particularly through the selection of wild versus cultivated strains, is another important factor in farm resilience. Wild strains provide greater environmental adaptability and disease resistance, while selected strains typically offer faster growth and higher yields. However, the reduced genetic diversity in clonal farming raises concerns about long-term sustainability. Research gaps identified include the need for long-term studies on the sustainability of farming techniques, particularly in the context of climate change, and more extensive investigations into the ecological and economic benefits of IMTA systems. Future research should focus on integrating biological, ecological, and economic aspects to optimize K. alvarezii farming and enhance its contribution to the blue economy